Education of national identity in primary forms: activity implemented by teachers - Skarbalius, Egidijus (Pedagogika, 2014)
In the present process of the development and changing of Lithuanian identity, the preservation of national identity becomes one of the most urgent socio-pedagogical problems. Research has proved that in the process of educating of the national identity among students and values of the ethnic culture the main responsibility lies on the school, and while observing the bent for ethnic culture among students of various age, it is seen that it is desirable by the youngest. The education of national identity should be started from the first form due to the thinking about the future, strengthening generation and family relations because students who do not obtain the basics of national identity and ethnic culture at primary school in later years encounter it too late and are emotionally unprepared to receive it. Nevertheless, there is a lack of scientific research analyzing the national identity of students from primary school forms. According to this, in 2012 the research was accomplished (by using the method of in-depth interviewing), in which 35 teachers of primary forms participated.